Ceftazidime-Avibactam in Combination With Fosfomycin: A Novel Therapeutic Strategy Against Multidrug-Resistant Pseudomonas aeruginosa. (17th May 2019) - Papp-Wallace, Krisztina M; Zeiser, Elise T; Becka, Scott A; Park, Steven; Wilson, Brigid M; Winkler, Marisa L; D'Souza, Roshan; Singh, Indresh; Sutton, Granger; Fouts, Derrick E; Chen, Liang; Kreiswirth, Barry N; et al.
Abstract: Previously, by targeting penicillin-binding protein 3, Pseudomonas -derived cephalosporinase (PDC), and MurA with ceftazidime-avibactam-fosfomycin, antimicrobial susceptibility was restored among multidrug-resistant (MDR) Pseudomonas aeruginosa . Herein, ceftazidime-avibactam-fosfomycin combination therapy against MDR P . aeruginosa clinical isolate CL232 was further evaluated. Checkerboard susceptibility analysis revealed synergy between ceftazidime-avibactam and fosfomycin. Accordingly, the resistance elements present and expressed in P . aeruginosa were analyzed using whole-genome sequencing and transcriptome profiling. Mutations in genes that are known to contribute to β-lactam resistance were identified. Moreover, expression of bla PDC, the mexAB - oprM efflux pump, and murA were upregulated. When fosfomycin was administered alone, the frequency of mutations conferring resistance was high; however, coadministration of fosfomycin with ceftazidime-avibactam yielded a lower frequency of resistance mutations. In a murine infection model using a high bacterial burden, ceftazidime-avibactam-fosfomycin significantly reduced the P . aeruginosa colony-forming units (CFUs), by approximately 2 and 5 logs, compared with stasis and in the vehicle-treated control, respectively. Administration of ceftazidime-avibactam and fosfomycin separately significantly increased CFUs, by approximately 3 logs and 1 log, respectively, compared with the number at stasis, and only reduced CFUs by approximately 1 log and 2 logs, respectively, compared with the number in the vehicle-treated control. Thus, the combination of ceftazidime-avibactam-fosfomycin was superior to either drug alone. By employing a "mechanism-based approach" to combination chemotherapy, we show that ceftazidime-avibactam-fosfomycin has the potential to offer infected patients with high bacterial burdens a therapeutic hope against infection with MDR P . aeruginosa that lack metallo-β-lactamases. Abstract : Multidrug-resistant (MDR) Pseudomonas aeruginosa is a serious public health threat. The ceftazidime-avibactam-fosfomycin combination possessed synergistic activity against MDR P . aeruginosa . A murine infection model validated the efficacy of this combination for MDR P . aeruginosa infections with high bacterial burdens.